The evaluation of outcome based education of teacher training program in Pakistan - Khan, Farah (2016)
Bachelor of Education (B.Ed.) program in Khyber Pakhtunkhwa (KP) Pakistan is vital in producing competence and quality teachers. However, this program is yet not up to the required level compared to international standard. Thus, a further study was conducted to identify the factors affecting the low level of B.Ed. program. Additionally, this study also aims to explore the appropriate contents and competencies needed to produce competence and quality teachers. A mixed-method approach was utilized to achieve the objectives of the study. A standardized questionnaire developed by the UNESCO and semi-structured interview protocols were used to collect data. A total of 357 respondents were chosen randomly from two districts namely Charsadda and Peshawar from Khyber Pakhtunkhwa (KP)-Pakistan to responds to the questionnaire. Apart from that, data were also gathered through semi-structured interview from 20 respondents and documents analyses. The quantitative and qualitative data were analyzed using descriptive statistics and themes respectively. The results found that the current B.Ed. teacher education program did not achieve the standard due to short of time, insufficient materials in libraries, infrastructure, information and communication technology equipment, and weak teaching practices. The study also found that the standard of the existing B.Ed. curriculum did not conform to the international standard. Thus, findings of the study suggested that course duration needs to be extended and suitable contemporary contents be include in the syllabus. Proper teachers training program, incentives and salaries for teachers also need to be considered. The level of teacher education program also needs to be addressed to meet the global challenges. This study has contributed to the development of the B.Ed. teacher education program in the context of KP-Pakistan. Apart from that, the findings of the study will guide the stakeholders to improve teacher education program in particular and education sector in general.